Feasibility analysis of a sustainable system for an Australian remote town - Ali, Liaqat; Shahnia, Farhad; Arefi, A.; Iu, H.; Fernando, T. (IEEE, 2018)
© 2017 IEEE. This paper compares various stand-alone power systems for the remote town of Mount Magnet in Western Australia and proposes the most feasible solution. In this area, most of the towns are supplied with stand-alone generators while a hybrid renewable energy power system is an alternative technique to the existing system for which a feasibility analysis is conducted in this paper. This research considers both environmental and economic aspects to design the most feasible hybrid power system. HOMER software is used to conduct the cost analysis considering different combinations of a diesel generator, wind turbines, photovoltaic systems, converters, and battery storage systems.